LASER PHOTOCOAGULATION FOR PROLIFERATIVE DIABETIC RETINOPATHY, SINGLE SPOT 532-nm vs MULTISPOT 577-nm: VERY SHORT TERM CLINICAL EFFICACY - Diego Valera-Cornejo; Jaime Quiroz-Mendoza; Alejandro Arias-Gomez; Marlon Garcia-Roa; Paulina Ramirez-Neria; Veronica Romero-Morales; Yolanda Villalpando-Gomez; Renata Garcia-Franco (International Journal of Retina, 2021)
ABSTRACT This study aimed to compare clinical efficacy of retinal laser photocoagulation using a 577-nm multi-spot laser with pulses of 20 ms versus conventional 532-nm single-spot laser treatment with pulses of 100 ms, on the same patient with proliferative diabetic retinopathy (PDR) during 6-weeks follow-up. We included 46 eyes of patients treated at the retina service of the Mexican Institute of Ophthalmology, Queretaro, Mexico. Pan-retinal photocoagulation (PRP) was performed on one eye (Group 1) using multi-spot PRP with the EasyRet® 577 diode laser (Quantel Medical, Cournon d’Auvergne, France). On the other eye (Group 2), laser treatment was performed by the conventional single spot method using the Oculight SL® 532 diode laser (IRIDEX Corporation, Mountain View, CA, The USA). The primary endpoint was absence of signs in which the disease was considered active at 6 weeks and the secondary outcomes included laser parameters, best-corrected visual acuity (BCVA), central macular thickness (CMT) at baseline, and 6 weeks and results of subjective pain analysis. There was no significant difference between both treatment groups regarding age, gender, BCVA or CMT at baseline. At 6 weeks, PDR activity was similar between the groups (47.8 % versus 56.5%; p =0.55). No significant difference in CMT and BCVA was observed between the groups throughout the study period. Patient-reported pain scores were similar between the groups (5.0 versus 5.8; p = 0.30). However, total time of procedure was significantly shorter in group 1 (12.9 minutes [min] versus 22.3 min; p < 0.001). No major adverse events were identified We concluded that laser photocoagulation of the retina with the use of the multi-spot technology in patients with PDR has similar short-term efficacy to that of conventional single spot retinal photocoagulation. The multi-spot laser required less time to complete the procedure with more spots delivered to compensate its lower fluency, showing similar patient tolerance.